2020
DOI: 10.1007/s41348-020-00327-9
|View full text |Cite
|
Sign up to set email alerts
|

Colletotrichum species causing cassava (Manihot esculenta Crantz) anthracnose in different eco-zones within the Recôncavo Region of Bahia, Brazil

Abstract: A survey to investigate the occurrence of cassava anthracnose disease (CAD) and distribution of Colletotrichum spp. in cassava plantations in different eco-zones of the Reconcavo Region in Bahia, Brazil, investigated during the rainy season of 2014. A total of 50 cassava fields distributed among 18 municipalities were visited and intensity of anthracnose evaluated. The highest disease incidence (DI) (83.3%) was in samples collected in São Félix, and the lowest (34.4%), in Varzedo. Municipalities that presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…No information exists in the literature on differences in aggressiveness among isolates of each of the five Colletotrichum species, although such differences have been reported for other species of the C. gloeosporioides complex (Wang et al, 2021). Liu et al, 2015;Diao et al, 2017;Sharma et al, 2017Sharma et al, , 2022de Silva et al, 2017b;Giblin et al, 2018;Chethana et al, 2019;Costa et al, 2019;Chaves et al, 2020;Chen et al, 2020;Chung et al, 2020;Mao et al, 2020;Yokosawa et al, 2020;Andrioli et al, 2021;Carbone et al, 2021;Luo et al, 2021;Moral et al, 2021;Oo et al, 2021;Han et al, 2022). However, these symptoms are similar to those caused by other Colletotrichum species belonging either to the C. gloeosporioides complex or to other Colletotrichum species complexes.…”
Section: Intraspecific Diversitymentioning
confidence: 99%
“…No information exists in the literature on differences in aggressiveness among isolates of each of the five Colletotrichum species, although such differences have been reported for other species of the C. gloeosporioides complex (Wang et al, 2021). Liu et al, 2015;Diao et al, 2017;Sharma et al, 2017Sharma et al, , 2022de Silva et al, 2017b;Giblin et al, 2018;Chethana et al, 2019;Costa et al, 2019;Chaves et al, 2020;Chen et al, 2020;Chung et al, 2020;Mao et al, 2020;Yokosawa et al, 2020;Andrioli et al, 2021;Carbone et al, 2021;Luo et al, 2021;Moral et al, 2021;Oo et al, 2021;Han et al, 2022). However, these symptoms are similar to those caused by other Colletotrichum species belonging either to the C. gloeosporioides complex or to other Colletotrichum species complexes.…”
Section: Intraspecific Diversitymentioning
confidence: 99%
“…Plants infected by C. plurivorum show symptoms of anthracnose, which include dark brown stem and fruit spots, stem cankers, pre‐ and post‐harvest fruit rot, leaf spots and wilt, shoot‐tip dieback and defoliation (Liu et al., 2019 ; de Oliveira et al., 2020 ). However, these symptoms are similar to those caused by other Colletotrichum species.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…In the areas of its current distribution, C. plurivorum is reported to cause anthracnose on its host plants. Disease symptoms include dark brown stem and fruit spots, stem cankers, pre‐ and post‐harvest fruit rot, shoot‐tip dieback, leaf spots, wilting of leaves and defoliation (Liu et al., 2019 ; de Oliveira et al., 2020 ). Yield losses caused by C. plurivorum vary a lot.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…These can lead to more than 90% defoliation and diseased fruits in China, resulting in a decline in both the quantity and quality of fruit, while simultaneously compromising the overall vitality of apple trees (Shan et al., 2021 ; Zhang et al., 2016 ). Aetiological studies have identified several Colletotrichum species ( C. aenigma , C. alienum , C. fiorinae , C. fructicola , C. gloeosporioides , C. karstii , C. nymphaeae , C. siamense and C. tropicale ) as causal agents of GLS (de Oliveira et al., 2020 ; Sharma et al., 2017 ; Velho et al., 2019 ; Wang et al., 2015 ). C. fructicola is the predominant pathogen among the Colletotrichum species causing GLS in China (Velho et al., 2019 ; Wang et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%